Stercorarius parasiticus (Stercorariidae) - Füttern eines Jungen - Georg Rüppell (IWF (Göttingen), 1968)
(en)The film shows the feeding of a young arctic skua Stercorarius parasiticus L. The begging chick is fed by the adult bird which had been brooding till then, and by its mate.